(untitled) (Journal of Accessibility and Design for All, 2020)
Indonesia elders have a choice to stay in residential or live in a nursing home. Effort should be invested to maintain the elderly well-being despite their lives choice. The purpose of this study is to observe Indonesian elderly who live in residential (either lives independently or with families) and nursing home. In addition, this study also describes the anthropometry of Indonesian elderly, in particular in relation to bedroom design for elderly. One hundred and three Indonesian elderly were involved in this study (mean age = 74.4 years, SD= 8.98 year, 82 female). A total of 15 anthropometry body dimensions are measured based on their relevance to the elder’s bedroom design. Results show different activities among Indonesian elders based on their dependencies. The bedroom design for Indonesian elderly is proposed.